Pendampingan Metode Pembiasaan dalam Meningkatkan Kemampuan Pelaksanaan Shalat Dhuha Siswa SDN 1 Cibeber Kec. Kiarapedes Kab. Purwsakarta - Muhammad Faisal Husain; Akke Azhar Annisa; Dede Supendi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Duha prayer is a sunnah prayer that is carried out in the morning starting from the rising of the sun until it is time for the dhuhur prayer. At SD Negeri 1 Cibeber, the dhuha prayer is taught during Islamic religious education (PAI) lessons, but students do not master the lafadz reading the dhuha prayer. The purpose of this study was to educate students of SD Negeri 1 Cibeber grade 3 so that they have the ability and understanding of the dhuha prayer both reading lafadz and procedures for dhuha prayer in accordance with applicable regulations. This service implementation method uses the PAR method which is carried out in stages: Problem identification is carried out as a first step to formulate what will be used as material for system planning and materials in educating in this service activity. Conducted a survey of SD Negeri 1 Cibeber where the activities were carried out. Then carry out the interview and discussion process with the teacher at SD Negeri 1 Cibeber to identify problems. The implementation of the solution or idea was carried out on 14 until 21 February, 2024 in the form of educating grade 3 students. perform the Duha prayer properly. By using this habituation method, it can improve students' ability to memorize the lafadz reading the dhuha prayer.